Social support needs of caregivers rearing children with severe motor and intellectual disabilities at home in Japan - Wakimizu, Rie; Fujioka, Hiroshi (Frontiers in Rehabilitation Sciences, 2024)
Background: In Japan, recently, the number of children with severe motor and intellectual disabilities (SMID) is steadily increasing. Caregivers such as parents and family members are struggling with how to live with their children at home and in the community after discharge.The current study aimed to explore the social support needs faced by caregivers while rearing the child with SMID in order to identify effective means of social support in Japan.We conducted a cross-sectional survey of the primary caregivers of children with SMID at home through special-needs elementary, junior high, and senior high schools nationwide, using a self-administered, anonymous questionnaire to investigate the actual social support needs of the caregivers. All statements of social support need were coded using Krippendorff content analysis.Results: Questionnaire returns were obtained from 1,176 families, and the descriptions of 1,173 families were included in the analysis. The results of the analysis showed that the needs of the caregivers consisted of seven categories.The social support needs expressed by the caregivers are necessary findings for Japan today, both for the soft side, such as the development of local systems and regulations to support these families, and for the hard side, such as the increase and improvement of facilities and equipment.